Mapping the Side-Chain Length of Small-Molecule Acceptors towards the Optimal Hierarchical Morphology in Ternary Organic Solar Cells - Zhou, Zichun; Xu, Shengjie; Zhu, Xiaozhang (Organic Materials, 2021)
Using multiple light-absorbing materials to realize a broader and better absorption spectrum in multi-component organic photovoltaics has achieved significant success to obtain high power conversion efficiency. Meanwhile, the good materials combinations with matched electronic structure and proper blend morphology for charge generation and transport are of primary importance for implementation of the multi-component strategy. Hierarchical morphology has been clearly demonstrated to improve all performance parameters in ternary organic photovoltaics but shows strong dependence on the molecular structures. Here we develop four small-molecule electron acceptors with different alkyl chain lengths to find the optimal solution of alkyl chain towards the defined hierarchical morphology and carry out a clear and comprehensive investigation of the alkyl chain length effects on the structure–morphology–device performance relationships in ternary blends. There is a positive correlation between the power conversion efficiencies of the four ternary systems and their short-circuit current density parameters, manifesting the significance of distinguishing optimal alkyl side chain length of small-molecule electron acceptors for defined hierarchical morphology to afford efficient carrier generation. The non-optimal side chains would retard the BTR crystallization and make the PC71BM domain sizes incontrollable, leading to a morphology without a defined hierarchy. Such a detailed mapping of the alkyl side chain length of small-molecule electron acceptors provides new insight into the materials combinations for the next-step high-performance multi-component organic photovoltaics.
Keywords: ternary organic solar cells; hierarchical morphology; side-chain modulation; small-molecule acceptors